The Treatment Status of Patients in NSCLC With RET Fusion Under the Prelude of Selective RET-TKI Application in China: A Multicenter Retrospective Research - Meng, Yan; Yang, Yilin; Fang, Yujia; Lin, Xinqing; Xie, Xiaohong; Deng, Haiyi; Wu, Jianhui; Zhou, Maolin; Sun, Ni; Xie, Zhanhong; Liu, Ming; Ouyang, Ming; et al. (Frontiers in Oncology, 2022)
Background: Rearranged during transfection (RET) fusion is a kind of uncommon mutation (about 1%) in non-small cell lung cancer (NSCLC). Although selective tyrosine kinase inhibitors (TKI) (Selpercatinib and Pralsetinib) have been available, there is no real-world data about the difference in the efficacy between RET-TKI and other regimens in China. Methods: We conducted a multicenter retrospective analysis of 49 patients with RET-fusion positive NSCLC. The characteristics and the clinical outcomes with RET-TKI, multi-kinase inhibitor (MKI), systematic chemotherapy and immune-checkpoint inhibitor (ICI)-based regimens were evaluated. Results: Of the 92 treatments in patients included, RET-TKI was administered 24 times (26.1%), systematic chemotherapy was 35 times (38.0%), ICI-based regimens was 26 times (28.3%) and MKI was 7 times (7.6%). RET-TKI had a higher objective response rate than the chemotherapy and ICI-based regimens (63.6% vs. 14.3% vs. 21.0%, p<0.001). The median progress free survival (mPFS) of RET-TKI, chemotherapy, immunotherapy, MKI were 16.9 (95% CI: 1.8-32.0) months, 11.9 (95% CI: 7.7-16.1) months, 6.7 (95% CI: 2.9-10.5) months, 2.77 (95% CI: 1.13-4.41) months, respectively. The mPFS of RET-TKI was longer than MKI and immunotherapy (p<0.001). But there was no statistically significant difference between RET-TKI and chemotherapy (p=0.096). Moreover, chemotherapy had longer mPFS than MKI. In subgroup analysis, patients with brain metastases in RET-TKI treatment had worse mPFS than the one of patients without brain metastases (p=0.012). For patients having chemotherapy with or without angiogenesis inhibitors, the mPFS was 12.0 (95%CI: 11.05-13.02) months and 9.1 (95% CI: 8.31-9.89) months (p=0.468). mPFS (4.7 (95% CI: 1.8-9.0) months vs 7.6 (95% CI: 1.1-14.0) months, p=0.910). In the group of ICI-based regimens, the expression level of PD-L1 did not affect the mPFS of ICI (PD-L1 (+) vs PD-L1 (-): 4.7 (95% CI: 1.8-9.0) months vs 7.6 (95% CI: 1.1-14.0) months, p=0.910). For overall patients, ECOG PS score, therapy lines and therapeutic regimens were the independent factors affecting the prognosis. Conclusions: In RET-fusion positive NSCLC, RET-TKI is the best choice for a better response rate and PFS. In addition, chemotherapy especially combined with angiogenesis inhibitors which may bring a good PFS is still a good choice for this group of patients.